RADICAL INNOVATIONS, BUSINESS COMPETITIVENESS AND DEPOSIT MONEY BANKS IN NIGERIA - NWAGU, UMUNNA GODSON; AKAH, NNENNA MARYRITA; UZOH, NNAEMEKA MARTIN (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2025)
Radical innovation fundamentally transforms markets, redefines industries, and alters our daily lives and work. The evolution of banking through innovation enhances payment processing, facilitating a transition from conventional banking practices to digital transformation. This study aims to explore the effects of radical innovations on the competitiveness of Nigerian deposit money banks from Q1 2009 to Q4 2023. The ARDL (autoregressive distributed lag) model was employed to assess long-term relationships. Unit root tests were performed on variables including return on assets, automated teller machines, internet banking, and mobile banking, revealing order one I(1) for the first three and order zero I(0) for point of sale. Co-integration-bound tests confirmed long-term relationships among the variables. The findings indicated that ATMs and mobile banking positively and significantly influence return on assets, while point of sale negatively impacts ROA. The study established a long-term relationship between the variables, with no serial correlation detected, indicating stability. It was concluded that radical innovations such as ATMs, PoS, internet banking, and mobile banking maintain a long-term relationship with Nigerian deposit money banks. Consequently, Nigerian deposit money banks are encouraged to invest in technology and innovative banking solutions to enhance ATM services, point-of-sale systems, internet banking, and mobile banking, thereby reducing customer congestion in banking halls.